1985
DOI: 10.1063/1.448286
|View full text |Cite
|
Sign up to set email alerts
|

Separation of temperature and density effects on collision-induced Rayleigh and Raman line shapes of liquid carbon disulfide

Abstract: Molecular dynamics study of liquid carbon disulfide and benzene: Effect of pressure on the farinfrared collisioninduced absorption J. Chem. Phys. 103, 9580 (1995); 10.1063/1.469973 Some aspects of collisioninduced transitions in spectral line shape experiments AIP Conf. Proc. 216, 269 (1990); 10.1063/1.39917 Temperature and density effects on the collisioninduced depolarized Rayleigh line shapes of liquid carbon disulfideQuantitative results for the separate temperature and density effects on collisioninduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The low-frequency components were attributed to reorientation, and the high-frequency components were assigned to gaslike translations. 24 Even though it is now known that reorientation dominates the entire DLS spectrum of carbon disulfide, 26−28 these pioneering studies nevertheless showed that density and temperature can in fact be separable in the low-frequency Raman spectrum of molecular liquids. Ladanyi et al used molecular dynamics (MD) and Monte Carlo simulations to evaluate the temperature and density dependences of the spectral moments of low-frequency Raman spectra of argon and xenon.…”
Section: Introductionmentioning
confidence: 99%
“…The low-frequency components were attributed to reorientation, and the high-frequency components were assigned to gaslike translations. 24 Even though it is now known that reorientation dominates the entire DLS spectrum of carbon disulfide, 26−28 these pioneering studies nevertheless showed that density and temperature can in fact be separable in the low-frequency Raman spectrum of molecular liquids. Ladanyi et al used molecular dynamics (MD) and Monte Carlo simulations to evaluate the temperature and density dependences of the spectral moments of low-frequency Raman spectra of argon and xenon.…”
Section: Introductionmentioning
confidence: 99%
“…By these spectroscopic techniques in time and frequency domains, intermolecular dynamics of a simple molecular liquid such as CS 2 , 5,6,11,25 halogenated methanes, 11,32,39 benzene 6,11,39 and its derivatives, 18,21 and more complicated hydrogen-bonded molecular liquid such as water, [22][23][24] alcohol, 16 ethylene glycol 19 and their solutions 8,9,20 has been studied. General agreement exists in the intermolecular dynamics in terms of relaxation modes and oscillation modes that are closely related to the microscopic environment in which the molecules are located.…”
Section: Introductionmentioning
confidence: 99%
“…First, we will present the experimental observations using Raman spectroscopy on the ν 1 -2ν 2 CO 2 Fermi dyad domain, followed by those on the induced (ν 2 and ν 3 ) and allowed (ν 1 and 2ν 2 ) modes of CS 2 . Then, we will rationalize these observations using the collision induced framework of Madden et al for the forbidden CS 2 modes, 18,20,21,[23][24][25][26][27][28][29][30][31][32]35 and vibrational relaxation models to discuss the departures from ideality probed by the allowed CO 2 and CS 2 modes. Finally, we will discuss the non ideality of the mixture from the existence of two distinct solvation regimes with a transition characterised by a plateau domain found in the evolution of the spectroscopic observables with the concentration.…”
Section: Fig 1 Pressure-composition Diagram Of the Binary Mixtures mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] In dense phase, the aim was to provide insight on the nature and time scale of the intermolecular interactions from "allowed" vibrational spectra or from the analysis of collision induced (CI) spectra which are unique probes of the multi-body interactions. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The study of the interaction of carbon dioxide with molecular liquids and complex fluids as ionic liquids is a field of current interest, motivated not only from the fundamental point of view but mainly under the impetuous motivation of understanding the interactions of CO 2 in the field of environmental studies. [67][68][69][70] Surprisingly, in this context, studies of the CO 2 -CS 2 binary mixture are extremely scarce.…”
Section: Introductionmentioning
confidence: 99%